Mengukur Output Gap Ekonomi Maluku Utara (Pendekatan Hodrick-Prescott Filter) - Jufri Jacob; Zulkifly Waibot (Future Science, 2022)
Development anywhere will always be faced with fluctuating conditions or the ups and downs of economic growth. In the discourse